1997
DOI: 10.1055/s-2008-1071069
|View full text |Cite
|
Sign up to set email alerts
|

Torsion of Spermatocele and Aplasia of the Vas Deferens. A Case Report

Abstract: Torsion of a spermatocele combined with aplasia of the vas deferens is described. The purpose of this case report is that this rare condition should not be omitted from the differential diagnosis of the acute scrotum in childhood. The authors also support that the term "spermatocele" could be used in the non semen producing age of childhood, based upon the non age-dependent pathologic criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Our case is unique in that he is the second youngest case of EC torsion in the literature. Liolios et al reported the youngest case (6 months old) of EC torsion ( 4 ). Moreover, this is also the fourth case of right EC torsion reported after Bleve et al ( 2 ), Ozaal et al ( 9 ) and Vafadar et al ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our case is unique in that he is the second youngest case of EC torsion in the literature. Liolios et al reported the youngest case (6 months old) of EC torsion ( 4 ). Moreover, this is also the fourth case of right EC torsion reported after Bleve et al ( 2 ), Ozaal et al ( 9 ) and Vafadar et al ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Пе-рекрут КПЯ встречается крайне редко, особенно у пациентов младшего возраста [3]. По данным иностранных источников, у детей было зарегистрировано 9 случаев изолированного перекрута КПЯ, среди которых 8 случаев были у детей пре-и пубертатного возраста, а один -у младенца [7]. В рамках данной публикации впервые описан случай сочетанного перекрута яичка и перекрута КПЯ у пациента 12 лет, который также может быть зарегистрирован и добавлен в литературу как десятый случай перекрута КПЯ.…”
Section: актуальностьunclassified
“…Most cysts are asymptomatic, although larger ones may cause scrotal discomfort, pain, or present as a mass. Exceptionally, patients present with acute scrotum secondary to torsion of the cyst [67][68][69] (Figs. 12.21-12.23).…”
Section: Simple Cystsmentioning
confidence: 99%